2018
DOI: 10.1002/adma.201706329
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystalline Precursors for the Co‐Assembly of Crack‐Free Metal Oxide Inverse Opals

Abstract: Inorganic microstructured materials are ubiquitous in nature. However, their formation in artificial self-assembly systems is challenging as it involves a complex interplay of competing forces during and after assembly. For example, colloidal assembly requires fine-tuning of factors such as the size and surface charge of the particles and electrolyte strength of the solvent to enable successful self-assembly and minimize crack formation. Co-assembly of templating colloidal particles together with a sol-gel mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 56 publications
1
40
0
Order By: Relevance
“…Formation of Titania IO Films : TiO 2 nanocrystals were synthesized by hydrolysis and polycondensation of titanium isopropoxide (TIP) in the presence of tetramethylammonium hydroxide (TMAH, CAUTION TMAH is highly toxic) …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Formation of Titania IO Films : TiO 2 nanocrystals were synthesized by hydrolysis and polycondensation of titanium isopropoxide (TIP) in the presence of tetramethylammonium hydroxide (TMAH, CAUTION TMAH is highly toxic) …”
Section: Methodsmentioning
confidence: 99%
“…A constant amount of TIP in isopropanol was typically added dropwise to the aqueous solution of TMAH at room temperature under stirring; the TMAH concentration was varied to achieve different ratios of TIP to TMAH ( R TIP/TMAH ). The reaction mixture was then heated and refluxed for ≈6 h. These nanocrystals were used directly in the colloidal assembly solution as the matrix precursor, without purification …”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[70][71][72] When compared with a monolayer 2D counterpart, 3DOM thin lms tend to be endowed with strengthened continuous connection channels, as well as improved avenues for conducting electrical signals. 73 The preparation of 3DOM metal oxides is oen based on the metal precursor solution impregnation. [74][75][76] Miyake et al recently reported a novel epitaxial growth process of single-crystal 3DOM…”
mentioning
confidence: 99%